Teachers Matter Improving Recruitment, Retention and Development of Teachers - See, Beng Huat; Morris, Rebecca (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book highlights the global concern about the teaching workforce, from recruitment and retention of teachers to the development and quality of teachers in schools. The collection of papers in this book is international in scope, representing a range of research designs (from longitudinal studies using national and international datasets, large-scale surveys, reviews and syntheses of evidence to randomized control trials, value-added models and design-based action research). These papers exemplify the high standard of research in education.